Parotid Gland Atrophy in Patients with Chronic Trigeminal Nerve Denervation - Raz, E.; Saba, L.; Hagiwara, M.; Hygino de Cruz, L.C.; Som, P.M.; Fatterpekar, G.M. (American journal of neuroradiology : AJNR, 2013)
Trigeminal nerve injury or dysfunction is associated with denervation atrophy of muscles innervated by the mandibular branch of the trigeminal nerve. The purpose of our study was to evaluate the association between chronic CN V denervation and parotid gland atrophy. Twenty-six patients with chronic masticator muscle atrophy were retrospectively identified and evaluated for the presence of ipsilateral parotid gland atrophy. Twenty-six age-matched control subjects with no clinical or imaging evidence of chronic masticator space atrophy were also identified. Segmentation of the parotid gland was performed to calculate a parotid asymmetry index. The Fisher exact test and t test were respectively used to determine the correlation between parotid gland atrophy and ipsilateral masticator muscle atrophy and to evaluate any difference in the size of the involved parotid gland when compared with that in the control subjects. Ipsilateral parotid gland atrophy was seen in 9/26 (42.8%) patients with fatty replacement of the masticator group of muscles, suggesting a correlation between parotid gland atrophy and CN V denervation (P<.001). The parotid asymmetry index was significantly different in patients with CN V denervation (0.59±0.25) compared with control subjects (0.92±0.03) (P<.001). Ipsilateral parotid gland atrophy can accompany chronic CN V denervation change, and its clinical significance remains to be determined.